Linguistic Attitudes of Andean Migrants in Sociodemographic Areas of Languages in Contact - Falcón Ccenta, Pedro (2020)
From a theoretical-mentalist perspective, identities, and linguistic attitudes of Andean migrants in the human settlement Villa Huanta, San Juan de Lurigancho (Lima, Peru) were evaluated. The qualitative and quantitative approaches allowed the measurement of the variables sex, age and schooling for which the questionnaire, participant observation and semi-structured interview were used in a complementary manner. A quantitative evaluation made it possible to determine that the Andean migrants did not show a very high value towards Spanish in relation to the Quechua language, especially in the affective sphere. However, from a qualitative perspective, this does occur in the cognitive and sociocultural spheres, not only among young people, but also in the adult population.